THE ROLE OF THE WAKALAH BIL UJRAH CONTRACT IN ENHACING THE EFFICIENCY OF ORDER BASED BUSINESSES IN CENRANA DISTRICT - Fera Pariska; Ismail Keri (Institut Agama Islam Negeri (IAIN) Bone, 2026)
Abstract This study aims to analyze the implementation of the wakalah bil ujrah contract and its role in improving the efficiency of the furniture and furniture business in Cenrana District. The research uses a descriptive qualitative approach through field studies. Data was collected through observation, interviews, and documentation of five informants consisting of business owners, intermediaries, and consumers. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that the implementation of the wakalah bil ujrah contract is in accordance with sharia principles through the application of trust, trust, effective communication, and the provision of ujrah based on agreement. The implementation of the contract is able to increase business efficiency through a clear division of tasks, expansion of marketing, increase in the number of orders, and reduce marketing costs and time. The main contribution of this study shows that the use of social media by intermediaries in the wakalah bil ujrah scheme is an important factor in increasing business efficiency without ignoring sharia principles. Abstrak Penelitian ini bertujuan menganalisis penerapan akad wakalah bil ujrah serta perannya dalam meningkatkan efisiensi usaha mebel dan furnitur pesanan di Kecamatan Cenrana. Penelitian menggunakan pendekatan kualitatif deskriptif melalui studi lapangan. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi terhadap lima informan yang terdiri atas pemilik usaha, pihak perantara, dan konsumen. Analisis data dilakukan menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penerapan akad wakalah bil ujrah telah sesuai dengan prinsip syariah melalui penerapan amanah, kepercayaan, komunikasi yang efektif, dan pemberian ujrah berdasarkan kesepakatan. Penerapan akad tersebut mampu meningkatkan efisiensi usaha melalui pembagian tugas yang jelas, perluasan pemasaran, peningkatan jumlah pesanan, serta pengurangan biaya dan waktu pemasaran. Kontribusi utama penelitian ini menunjukkan bahwa pemanfaatan media sosial oleh pihak perantara dalam skema wakalah bil ujrah menjadi faktor penting dalam meningkatkan efisiensi usaha tanpa mengabaikan prinsip-prinsip syariah.